Penerapan Strategi Behavior Dalam Peningkatan Akhlak Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di Sekolah SMA Negeri 1 Air Putih - Arrifa, Azril; Muhklis; Rambe, Masrina (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This study discusses the Strategy of Islamic Religious Education teachers in improving students' morals at SMA Negeri 1 Air Putih. Given the current lack of student morals. A simple example, when students meet or meet face to face with teachers, the students do not want to greet and reprimand the teacher. And such as swearing, being lazy to worship, fighting, mocking each other, fighting teachers Therefore, the author raised this title as a thesis research. The research method used is a descriptive qualitative research method using a descriptive qualitative research type. Data collection techniques in this study are observation, documentation, and interviews. The author hopes that with this research. The author also hopes that the results of this study can be useful for interested parties and can be a reference for further research.